Building form in Iraqi orchestra music compositions (Journal of the College of Basic Education, 2022)
Building form in Iraqi orchestra music compositions. The research aims to detect buildingFigure in the compositions of orchestral music in the works of Iraqi authors for the full orchestraMusical compositions written for small groups such as quartet or distribution are excludedMusic or forms that contained choir groups